Chiral iridium(iii) complexes with four-membered Ir–S–P–S chelating rings for high-performance circularly polarized OLEDs. Issue 57 (24th June 2019) - Yan, Zhi-Ping; Liao, Kang; Han, Hua-Bo; Su, Jian; Zheng, You-Xuan; Zuo, Jing-Lin
Abstract : CP-OLEDs with two series of chiral iridium(iii ) complexes based on four-membered Ir–S–P–S chelating rings and chiral BINOL-based derivatives show excellent electroluminescence performances with obvious CPEL properties. Abstract : Two series of chiral cyclometalated iridium(iii ) complexes based on sulfur atom containing enantiopure BINOL derivatives were rapidly synthesized, which are endowed with varied chiroptical properties. Moreover, the circularly polarized OLEDs using enantiomers show a maximum luminance of above 40 000 cd m −2 and an external quantum efficiency of 23.6% with low efficiency roll-off as well as obvious CPEL properties.